DDEL-12. NANOPARTICLE DELIVERY OF DOXORUBICIN FOR THE TREATMENT OF DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG) - Ung, Caitlin (Neuro Oncol, 2020)
DIPGs are the most aggressive pediatric brain tumors. Currently, the only treatment is irradiation but due to its palliative nature patients die within 12 months. Effective delivery of chemotherapy across the blood-brain barrier (BBB) has been a key challenge for the eradication of this disease. We have developed a novel gold nanoparticle functionalised with human serum albumin (Au-NP, 98.8 ±19 nm) for the delivery of doxorubicin. In this study, we evaluated the cytotoxic efficacy of doxorubicin delivered through gold nanoparticles (Au-NP-Dox). We found that DIPG neurospheres were equally sensitive to doxorubicin and Au-NP-Dox (at equimolar concentration) by alamar blue assay. Colony formation assays demonstrated a significantly more potent effect of Au-NP-Dox compared to doxorubicin alone, while the Au-NP had no effect. Furthermore, western blot analysis indicated increased apoptotic markers cleaved Parp, caspase 3/7 and phosphorylated H2AX in Au-NP-Dox treated DIPG neurospheres. Live cell content and confocal imaging demonstrated significantly higher uptake of Au-NP-Dox compared to doxorubicin alone. Treatment of a DIPG orthotopic mouse model with Au-NP-Dox showed no signs of toxicity with stable weights being maintained during treatment. However, in contrast to the above in vitro findings the in vivo study showed no anti-tumor effect possibly due to poor penetration of Au-NP-Dox into the brain. We are currently evaluating whether efficacy can be improved using measures to open the BBB transiently. This study highlights the need for rigorous in vivo testing of new treatment strategies before clinical translation to reduce the risk of administration of ineffective treatments.